The Influence of Workload, Burnout and Subjective Well Being on Employee Performance With Organizational Citizenship Behavior As An Intervening Variable in RSUD Dr. Mohammad Zyn Sampang District - Romaji; Mujanah, Siti; Sumiati (PT Inovasi Pratama Internasional, 2024)
The purpose of this study was to determine the effect of workload, burnout, subjective well-being (OCB) on employee performance at Dr. Hospital. Mohammad Zyn, Sampang Regency. Total sampling (saturated sampling) was used as the sampling technique. The research sample consisted of 70 respondents. Collecting data by distributing questionnaires to all respondents. The collected data were then analyzed using the PLS-SEM analysis technique. The results showed that workload had a positive and significant effect on (OCB). Workload has a positive and significant effect on employee performance. Burnout has a negative and significant effect on Organizational Citizenship Behavior (OCB). Burnout has no significant effect on employee performance. Subjective well-being has a positive and significant effect on (OCB). Subjective well being has a positive and significant effect on employee performance. Organizational Citizenship Behavior (OCB) has a positive and significant effect on employee performance